Liver Activity, Diseases And Disease Prevention (The Peerian Journal, 2022)
The article focuses on the liver, one of the internal organs of living organisms. The liver is one of the largest organisms in the body. It helps digest food, synthesizes the energy needed for life, and removes toxins from the body. The liver plays an important role in the production of bile, digestion and blood. In doing so, the liver uses a protected product to neutralize toxins that are formed or added to the food. If the liver fails, it will inevitably lead to death.